Effect of Citric Acid-Modified Chitosan on Hydration Regulation and Mechanism of Composite Cementitious Material System - Liguo Wang; Zhibin Qin; Jiandong Wu; Guangxia Sheng; Han Wang; Kai Liu; Xiaobin Dong; Fengjuan Wang; Jinyang Jiang (Buildings, 2023)
The temperature stress caused by the large temperature difference is the main factor causing harmful cracks in large-volume concrete. The introduction of admixtures is beneficial to reduce the temperature difference inside and outside the large-volume concrete. This study investigated the mechanism of how citric acid-modified chitosan (CAMC) affects the hydration heat release process and hydration products of composite cementitious materials. Through methods such as hydration heat, X-ray diffraction (XRD), mercury intrusion porosimetry (MIP), scanning electron microscopy (SEM), and nuclear magnetic resonance (NMR), the mechanism of how CAMC controls the hydration heat release process and hydration products of composite cementitious materials was revealed. The results show that the addition of CAMC delayed the hydration process of cementitious materials without affecting the type of hydration products but affected the content of each phase of hydration products. As the hydration process proceeded, the total porosity of all samples decreased, the volume of large pores decreased, and the volume of small pores increased. As the content of CAMC increased, the pore diameter of the hardened paste gradually became smaller, the proportion of large pores decreased, and the later hydration microstructure became more dense. The increase in CAMC dosage resulted in a decrease in the peak intensity of Q2 in the paste, indicating that Al atoms in Q2 (1Al) existed in the form of Alcoordination, which proves that CAMC reduced its hydration degree and delayed cement hydration.